Revised genebank standards for management of plant genetic resources - TYAGI, RISHI KUMAR; AGRAWAL, ANURADHA (The Indian Journal of Agricultural Sciences, 2015)
Genebanks are storehouses of genetic resources which have the primary responsibility of collecting, regenerating, conserving, characterizing, evaluating, documenting and distributing germplasm. With reference to plant genetic resources (PGR), today over 1,750 genebanks have been established worldwide, wherein 7.4 million accessions are maintained as ex situ collections in either seed banks, field genebanks, in vitro genebanks and/or cryogenebanks. To ensure that PGR are conserved in genebanks under recognized and appropriate conditions globally, the United Nations Food and Agriculture Organization (FAO) in collaboration with the International Board of Plant Genetic Resources (IBPGR) published the original Genebank Standards in 1994. Subsequently with advancements in science and technology, and changes in policy issues related to genetic resources, a need arose to revise the Genebank Standards. A consortium of global, regional and national stakeholders led by the FAO, Bioversity International, Global Crop Diversity Trust (GCDT), International Treaty on Plant Genetic Resources for Food and Agriculture (ITPGRFA) and International Plant Protection Convention (IPPC) prepared the revised version of the Genebank Standards. During the Fourteenth Regular Session of the Commission on Genetic Resources for Food and Agriculture (CGRFA) of the FAO the document on revised Genebank Standards was endorsed on 18 April 2013 and subsequently published as Genebank Standards for Plant Genetic Resources for Food and Agriculture. These revised genebank standards have a universal value and utility in guiding genebank management for seeds (orthodox and non-orthodox) and vegetatively propagated crops. It can be used by genebank curators as a source of guidance for developing standard operating procedures. We have compared the draft revised Genebank Standards (2013) with the original Genebank Standards (1994) to highlight the key features, along with some historical account on genebanks and development of standards.